Gender Identity Construction in Cyberspace: A Netnographic Analysis of Tinder Users - Andreas, Rino; Septiyanti, Nisa Dwi; Maulana, Mahesa (Sawwa: Jurnal Studi Gender, 2025)
Tinder is one of the virtual spaces that allows individuals to negotiate and present themselves dynamically. Stereotypes and traditional social norms continue to influence how gender is understood and represented online, which in turn reinforces problematic biases in interactions in digital spaces. This study aims to analyze the construction of gender identity among Tinder dating app users within the framework of a digital society. Employing a qualitative method with a netnographic approach, this research involves the researcher's active participation in the Tinder platform's virtual space by observing 52 user accounts and conducting in-depth interviews with five informants. The findings reveal that Tinder users construct gender identity through visual and textual elements, including profile photos, brief bios, hobbies, and interests. Gender identity on the platform can be manipulated and diversified to represent themselves as "women" and or "men." It underscores the necessity for contextualization and redefinition of gender identity within cyberspace. The study makes a significant contribution by revealing how gender identity on Tinder challenges traditional binaries through performative practices that blur the rigid boundaries between “feminine” and “masculine” while offering new insights into gender fluidity within digital spaces as arenas for renegotiating social norms.